Impact of the Agricultural Sector on Unemployment, Inequality and Rural Poverty: A Panel Regression Analysis in Indonesian Provinces - Suparman, Suparman; Sutomo, Maskuri; Anwar, Chairil; Olilingo, Fahrudin Zain (International Journal of Economics and Financial Issues, 2024)
This study examined how the agricultural sector impacted unemployment, income inequality, and rural poverty across Indonesia’s provinces from 2015 to 2021. Using data from the Central Bureau of Statistics (BPS) and a panel regression model, the research analyzed the relationships between these factors. It also explored the structural changes caused by the COVID-19 pandemic in 2020-2021. The findings showed that the agricultural sector’s Gross Regional Domestic Product (GRDP), farmer exchange rates, and informal labor significantly influenced unemployment and income inequality in rural areas. However, the pandemic did not have a major effect on income inequality or poverty levels in these areas. The GRDP and value-added in agriculture played a crucial role in reducing rural poverty. The findings also showed that the COVID-19 pandemic did not directly increase or decrease the number of poor people, but it affected informal agricultural workers due to physical distancing measures. The research highlighted the agricultural sector’s importance in addressing unemployment and inequality during the pandemic in Indonesia.